Heisenberg and Bohr in the sight of Frayn and Volpi - Víquez Jiménez, Alí (2014)
This article compares the literary interpretations of the relationship between Werner Heisenberg and Niels Bohr as presented in Michael Frayn’s Copenhague (theatrical work, 1998) and Jorge Volpi’s En busca de Klingsor (novel, 1999). Particular emphasis is placed on the controversial encounter between these two scientists in 1941, and likewise on the literary rendition of specifically scientific issues in the two texts under consideration.